THE EFFECT OF NOISE AND WORK PERIOD TO HEARING THRESHOLD VALUE IN TEXTILE INDUSTRY WORKERS - Sumardiyono Sumardiyono; Hartono Hartono; Ari Probandari; Prabang Setyono (Universitas Darussalam Gontor, 2018)
World Health Organization (WHO) data in 2012 states that 260 million or about 5.3% of the world's population was deaf. Ninety-one percent of them were adults and the rest were children. 20-30% of deafness can be triggered by noise which usually occurs in industrial workers. The impact of persistent noise can have temporary or permanent deafness. The aims of this research was to determined the effect of noise and work period to Hearing Threshold Value (HTV).Methods of this research used analytic observational (cross sectional approach). The population of research was textile industrial workers in PT. Iskandar Indah Printing Textile Surakarta. Sampling using cluster random sampling technique. Inclusion criteria: minimum 1 year working life, over 20 years of age, lack of discipline using ear protection. The number determination of samples used the difference formula average of two groups, then the number of subjects = 180 people.In this research noise intensity 66,8-98,4 dBA, mean of worker HTV with work period less than 10 years 29,8 dB, mean of worker HTV with work period more than 10 year 38,3 dB. The result of statistical test by Ancova Test, the noise effect on THV (F = 23,254; p = 0,018), influence of worked period to THV (F = 96,599, p = 0,000), and jointly noise and work period effect on THV (F = 65,507; p = 0,000). Long exposure to noise will increase Hearing Threshold Value of labor. Keywords: Noise, Work Period, Hearing Threshold Value